Pengaruh Pola Asuh Orangtua terhadap Pembentukan Karakter Anak Usia Dini - Rostinah (Maximal Journal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya dan Pendidikan, 2024)
Early childhood education is education after the birth of a child that cannot be ignored because early childhood can be a place where children can develop optimally according to their developmental characteristics. This research aims to see what influence parental parenting styles have on the formation of children's character. This research method uses literature review research with a textual qualitative approach. Data is collected by documentation, then the data obtained is critically analyzed. The research results obtained show that there are two themes regarding parenting styles in instilling children's character, including: the importance of character formation in the family and the impact of parenting styles on children's social character. The implications of this research can be used as a reference regarding understanding parenting styles that need to be used so that the use or application of parenting patterns that are not appropriate to the child's characteristics can be avoided